2005
DOI: 10.1021/jm0492960
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin Activation by Nonsulfated, Non-Polysaccharide Organic Polymer

Abstract: Accelerated antithrombin inhibition of procoagulant enzymes has been exclusively achieved with polysulfated polysaccharides. We reasoned that antithrombin activation should be possible with nonsulfated activators based only on carboxylic acid groups. As a proof of the principle, linear poly(acrylic acid)s were found to bind to antithrombin and accelerate inhibition of factor Xa and thrombin. Our work demonstrates that molecules completely devoid of sulfate groups can activate antithrombin effectively and, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…In contrast, the antithrombin affinities of non-saccharide ligands, e.g. small aromatic sulfates such as ECS and CS (19,32) and larger polymers such as polyacrylic acids (33,34), have been measured using 6-p-toluidinylnaphthalene-2-sulfonate, an external probe. In this study, we found that the interaction of our synthetic DHPs with antithrombin resulted in a decrease in intrinsic tryptophan fluorescence (Fig.…”
Section: A Specific Sulfated Dhp Sdso3 Preferentially Inhibits Factmentioning
confidence: 99%
“…In contrast, the antithrombin affinities of non-saccharide ligands, e.g. small aromatic sulfates such as ECS and CS (19,32) and larger polymers such as polyacrylic acids (33,34), have been measured using 6-p-toluidinylnaphthalene-2-sulfonate, an external probe. In this study, we found that the interaction of our synthetic DHPs with antithrombin resulted in a decrease in intrinsic tryptophan fluorescence (Fig.…”
Section: A Specific Sulfated Dhp Sdso3 Preferentially Inhibits Factmentioning
confidence: 99%
“…Using the K LAH value determined independently, the equilibrium dissociation constant of the PAA3450-antithrombin interaction (K PAA3450 ) was calculated to be 1.2 µM, which compares favorably with the value determined in direct titration (1.3 µM). 13 PAA-Accelerated Inhibition of Thrombin in the Presence of EFGH''. To test whether PAA interacts with PBS, we determined the influence of the tetrasaccharide EFGH′′ on the PAA-promoted antithrombin inhibition of thrombin.…”
Section: Acceleration Of Thrombin Inhibition By Paa2280mentioning
confidence: 99%
“…13 The PAA molecules, having no resemblance to a heparinlike polysaccharide scaffold but possessing a charge density comparable to heparin, increased the secondorder rate constant of factor Xa and thrombin inhibition several hundred-fold ( Figure 1). This was in striking contrast to other carboxylate polymers, poly(Asp) and poly(Glu), that have been known to display poor antithrombin activation properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition a number of investigators have shown that polymers exposing carboxylic groups at the surface have relatively good blood-contacting features. These materials may even exhibit "heparin mimic" properties [17][18][19] and thus enhance the antithrombogenicity of the biomaterial.…”
Section: Introductionmentioning
confidence: 99%